2011
DOI: 10.1139/b11-032
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards a reference genome for sunflower

Abstract: The Compositae is one of the largest and most economically important families of flowering plants and includes a diverse array of food crops, horticultural crops, medicinals, and noxious weeds. Despite its size and economic importance, there is no reference genome sequence for the Compositae, which impedes research and improvement efforts. We report on progress toward sequencing the 3.5 Gb genome of cultivated sunflower ( Helianthus annuus ), the most important crop in the family. Our sequencing strategy combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 50 publications
2
70
0
Order By: Relevance
“…For example, empirical studies of genomic divergence often report higher levels in regions of low recombination 25 . Recombination rates across the sunflower genome were inferred by comparing our high-density genetic map to a physical map recently developed for H. annuus 23,26 ( Supplementary Figs S5 and S6). We found that overall, recombination rates were negatively correlated with F ST (r 2 ¼ 0.14, Pearson correlation coefficient test, P-value o2.2e À 16, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, empirical studies of genomic divergence often report higher levels in regions of low recombination 25 . Recombination rates across the sunflower genome were inferred by comparing our high-density genetic map to a physical map recently developed for H. annuus 23,26 ( Supplementary Figs S5 and S6). We found that overall, recombination rates were negatively correlated with F ST (r 2 ¼ 0.14, Pearson correlation coefficient test, P-value o2.2e À 16, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the genes actually involved in the character are known only in a few cases. A new step forward for sunflower in 2010 was the International sequencing initiative, led by Rieseberg at British Columbia University, Canada (a return of Canada to the sunflower research scene), together with American, French and Argentinean collaboration (Kane et al, 2011). Using the Illumina/454 technique, the sequence of the USDA inbred line HA412OL should be available very soon, together with those of two French lines (XRQ and PSC8), sequenced by INRA using the new technique PacBio.…”
Section: Genomic Developments To Boost Sunflower Research and Breedinmentioning
confidence: 99%
“…This higher alignment percentage stresses the importance of the genome because oil palm has a complete genome sequence (Singh et al 2013) while the current assembly of the sunflower genome represents only 85 % of the complete genome. Although the draft genome of sunflower is not complete, the assembled genome is highly accurate and contiguous because most (more than 76 %) of the contigs larger than 5 kb were assigned to the physical and/or genetic map (Kane et al 2011). The present study implemented the GBS approach for SNP discovery in sunflower.…”
Section: Gbs and Snp Identificationmentioning
confidence: 99%